Pengaruh Kegiatan Mewarnai Gambar terhadap Kemampuan Motorik Halus Anak Kelompok B di Pendidikan Anak Usia Dini Bukit Selanjut Kecamatan Kelayang Kabupaten Indragiri Hulu - Ilham Kurnia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study aims to determine the effect of image coloring activity on fine motor group B children in PAUD Bukit Selanjut Kelayang Sub-district Indragiri Hulu Regency. This research is an experimental research using one-group pretest-posttest design to know comparison before and after treatment. Subjects of this study amounted to 7 children, with the objects is the influence of picture coloring activities on motor fine capabilities of group B Children in PAUD Bukit Selanjut Kelayang Sub-district Indragiri Hulu Regency. The population of this research is students in kindergarten PAUD Bukit Selanjut Kelayang Sub-district Indragiri Hulu Regency amounting to 13 children, whith a sample of 7 children consisting 4 from a man dan 3 from a woman. The sample is done by purposive sampling technique, that is by determining the sample through certain consideration. Data collection techniques used are test, observation and documentation. While the technique of data analysis using t-test test using SPSS Windows ver. 17. The results showed that thitung = 27,000 with Sig = 0,000. Because sig value <0,05 and thitung = 27,000 bigger than ttabel = 2,447, it can be concluded that there is significant influence after giving treatment in picture coloring activity. so Ho is rejected Ha accepted which means there is influence before and after being treated to fine motor abilities of children. The influence of picture coloring activity on fine motor ability of group B children in PAUD Bukit Selanjut Kelayang Sub-district Indragiri Hulu Regency is 56,25% (in medium category).Keywords: Smooth Motor Capability, Picture Coloring Activity